IgG4-related inflammatory pseudotumor of the renal pelvis involving renal parenchyma, mimicking malignancy. Issue 1 (December 2016) - Park, Ho; Kim, Kyoung
Abstract Background IgG4-related disease is a recently recognized systemic disease characterized by storiform fibrosis with infiltration of IgG4-positive plasma cells. In rare incidences, IgG4-related renal disease can present as a solitary mass lesion at renal pelvis and can pose a diagnostic challenge since these lesions mimic malignancy. Herein, we present a rare case of IgG4-related disease presenting as inflammatory pseudotumor lesion, involving the renal pelvis and also neighboring renal parenchyma. Case presentation A 75-year-old man with no history of IgG4-related disease underwent computed tomography (CT) scan for evaluation of prostatic cancer. The CT scan incidentally revealed a mass lesion located at the right renal pelvis. Radiologic findings were highly suggestive of malignancy. Therefore, the patient underwent right nephroureterectomy. Microscopically, the mass lesion showed storiform fibrosis with diffuse and intense inflammatory cell infiltration. Infiltrating cells were mainly histiocytes and plasma cells. Tubulointerstitium adjacent to the lesion also showed fibrosis with abundant plasmacytic infiltration. Immunohistochemical staining revealed the presence of IgG4-positive plasma cells in both the mass lesion and tubulointerstitium (mean of 94/HPF per field). Conclusion Considering these findings, we diagnosed the mass lesion as IgG4-related inflammatory pseudotumor of the renal pelvis. In patients with renal pelvic masses, IgG4-related inflammatory pesudotumor should be considered in the differential diagnosis to avoid unnecessary surgical intervention.